Chronic indeterminate phase of Chagas’ disease: mitochondrial involvement in infection with two strains - Baez, Alejandra Lidia (2013)
Chagasic cardiopathy has become one of the most frequent causes of heart failure and sudden death, as well as one of the most common causes of cardio-embolic stroke in Latin America. The myocyte response to oxidative stress involves the progression of cellular changes, primarily targeting the mitochondria and modifying therefore the energy supply. In this paper we analysed the effect of the infection of mice with 2 different strains of Trypanosoma cruzi (Tulahuen and SGO Z12) in the chronic indeterminate stage (75 days post-infection), upon the structure and function of cardiac mitochondria. The structural results showed that 83% of the mitochondria from the Tulahuen-infected mice presented an increase in their matrix and 91% of the mitochondria from the SGO Z12-infected group showed a reduction in their diameter (P< 0·05). When the Krebs cycle and mitochondrial respiratory chain functionality was analysed through the measurement of the citrate synthase and complexes I to IV activity, it showed that their activity was altered in all cases in a similar manner in both infected groups. In this paper we have demonstrated that the chronic indeterminate phase is not ‘silent’ and that cardiac mitochondria are clearly involved in the genesis and progression to the chronic chagasic cardiopathy when different factors alter the host-parasite equilibrium.